Nematic quantum phases in the bilayer honeycomb antiferromagnet - Zhang, Hao (2018)
The spin-1/2 Heisenberg antiferromagnet on the honeycomb bilayer lattice is shown to display a rich variety of semiclassical and genuinely quantum phases, controlled by the interplay between intralayer frustration and interlayer exchange. Employing a complementary set of techniques, comprising spin rotationally invariant Schwinger boson mean-field theory, bond operators, and series expansions, we unveil the quantum phase diagram, analyzing low-energy excitations and order parameters. By virtue of Schwinger bosons we scan the complete range of exchange parameters, covering both long-range-ordered and quantum disordered ground states, and reveal the existence of an extended, frustration-induced lattice nematic phase in a range of intermediate exchange unexplored so far.